Epidemiology of primary angle-closure glaucoma in the Russian Federation - V. V. Neroev; T. N. Malishevskaya; S. Yu. Petrov; S. M. Kosakyan; E. K. Zakharova (Российский офтальмологический журнал, 2025)
Purpose of the work: to study the epidemiological features of primary angle-closure glaucoma (PACG) in the constituent entities of the Russian Federation taking into account the risk factors for the development of the disease in different regions of the country. Material and methods. The analysis of the epidemiological indicators of PACG in the constituent entities of the Russian Federation was carried out: the absolute number of patients, the relative number per 100 thousands of the region’s population, the share of PACG as a percentage of all glaucoma, socio-demographic characteristics (gender, average age of disease onset), anatomical features of the eye structure as a factor in the closure of the anterior chamber angle, the frequency of an acute attack of glaucoma, as well as the principles of PACG treatment. Results. The absolute number of patients with PACG in the studied regions of the Russian Federation is 50,857 people, the relative number per 100 thousands of the population of the studied entities is 33.7, the share of PACG in all glaucoma is 8.2 %. Analysis of the indicators in the regions of the Russian Federation revealed the highest absolute number of patients with PACG in the Tyumen Region (7,829 people), St. Petersburg (7,500), Kaliningrad Region (6,117) and the Sakha Republic (Yakutia) (5,562). The relative number indicators per 100 thousand population are also higher in the Sakha Republic (Yakutia) (759.3), Kaliningrad (738) and Tyumen Regions (486.7). The share of PACG as a percentage of all glaucoma is highest in the Sakha Republic (Yakutia) (51.4 %) and Tyumen Region (22 %). PACG prevails in women (66.6 %), the average age of disease onset was 59.5. Conclusion. The obtained results, consistent with the data of numerous international studies, allow us to assess the current situation with PACG in the country for timely prevention, diagnosis and treatment of this disease.